THE COMBINE CREAM MIXTURE OF NIGELLA SATIVA AND OLEA EUROPAEA FASTEN THE BURN HEALING PROCESS WITH MINIMAL SCAR - Sony Noegroho; Taufiq R Nasihun; Wiratno Wiratno; Awal Prasetyo (Faculty of Medicine Diponegoro University, 2017)
Background: The healing process of burns is influenced by epithelial faster grown, VEGF expression (vascular endothelial growth factor) and the amount of collagen. Nigella sativa oil could cure the second grade burn wound as effective as silver sulfadiazine cream. Olea europaea accelerates the formation of collagen, reepitelisation and enhances VEGF expression. The combination of both proved its potential in producing faster wound healing with minimal scarring. Method: This is a true experimental study using “posttest only control group design”, including 40 males Wistar rats as subject, body weight ± 200 grams, and maintained at room temperature 280-320C, standard feed and ad libitum drink, adapted and acclimatized a week in Individual cages before treatment. All rats were induced burns in the back area with previous local anesthesia given. All rats are administered cream therapy immediately after burning induction, and repeated daily once for 5 days, and divided into 4 group with the treatment as follows; Group 1 were applied with Sulfadene® (silver sulfadiazine 1%), group 2 by Nigella sativa cream, Group 3 has given olive oil 5% and group 4 has given combination cream of Nigella sativa and olive oil 5%. On the 5th day of the study, each group was randomly assigned 5 rats to terminate the VEGF expression and counting the amount of fibroblast. The 21st day of the study, all groups were terminated and histopathologic examination of scar formation in scar burn areas measured in thickness with Optilab Pro® software.Result: The highest number of fibroblast cells was consecutive group 1 (27.4), group 3 (26.7), group 2 (26.4), and the least group 4 (18.3). VEGF expression did not differ in all groups (Kruskal Wallis, P = 0.074.Conclusion: The combination of Nigella sativa and Olea europea cream mixes speeds the healing of burns with scarring. Keywords: Nigella sativa, Olea europe, fibroblast, VEGF, burns, scar thickness